2020
DOI: 10.1002/mbo3.1034
|View full text |Cite
|
Sign up to set email alerts
|

Urban and agricultural soils in Southern California are a reservoir of carbapenem‐resistant bacteria

Abstract: Carbapenems are last‐resort β‐lactam antibiotics used in healthcare facilities to treat multidrug‐resistant infections. Thus, most studies on identifying and characterizing carbapenem‐resistant bacteria (CRB) have focused on clinical settings. Relatively, little is still known about the distribution and characteristics of CRBs in the environment, and the role of soil as a potential reservoir of CRB in the United States remains unknown. Here, we have surveyed 11 soil samples from 9 different urban or agricultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 71 publications
0
3
1
Order By: Relevance
“…Regarding the Gram-positive CRB isolated in this study, seven out of eight were Enterococcus sp., and one isolate was preliminarily identified as Paenibacillus lautus (Figures 7 and 8). Interestingly, no Gram-positives were identified in our previous water study [43], although we found Enterococcus species in our survey for CRB in soil [44], which usually has a larger bacterial load. Our findings in this study suggest that the broader type of ecosystems sampled here, and especially the addition of an enrichment step (seven out of the eight Gram-positive CRB were obtained from the sub-samples subject to enrichment), contributed to the better isolation of Gram-positive CRB.…”
Section: Distribution Abundance and Isolation Of Carbapenem-resistant...contrasting
confidence: 67%
See 2 more Smart Citations
“…Regarding the Gram-positive CRB isolated in this study, seven out of eight were Enterococcus sp., and one isolate was preliminarily identified as Paenibacillus lautus (Figures 7 and 8). Interestingly, no Gram-positives were identified in our previous water study [43], although we found Enterococcus species in our survey for CRB in soil [44], which usually has a larger bacterial load. Our findings in this study suggest that the broader type of ecosystems sampled here, and especially the addition of an enrichment step (seven out of the eight Gram-positive CRB were obtained from the sub-samples subject to enrichment), contributed to the better isolation of Gram-positive CRB.…”
Section: Distribution Abundance and Isolation Of Carbapenem-resistant...contrasting
confidence: 67%
“…To identify carbapenemase-producing CRB isolates, we utilized the CarbaNP assay as previously described [43,44] to detect carbapenem hydrolysis. Briefly, we performed the CarbaNP assay [56][57][58] following the CLSI guidelines [48] and using 6 mg/mL of meropenem.…”
Section: Identification Of Carbapenemase-producing Crb Isolatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The CRB are the main focus of bio-medical scientists due to the emergence of these bacteria as human pathogens. However, new research focuses are arising concerning their distribution within soil and water environments [46][47][48], as well as in waste-treatment plants [49]. Reports of CRB in soil are relatively scarce [47], but to our knowledge, no studies exist that focused on their survival rate in the soil following wildfires.…”
Section: Discussionmentioning
confidence: 99%